Nicotine reduces cell viability and induces oxidative stress in human gingival fibroblasts - Azmi, Sabrina; Hadi, Restu Syamsul; Kusuma, Indra; Suciati, Yulia; Sari, Wening (Faculty of Medicine, Universitas Trisakti, 2024)
BackgroundNicotine, as the main component of cigarettes, is known to interfere with the proliferation of human gingival fibroblasts (HGFs) and can trigger oxidative stress. This study aimed to analyze the impact of nicotine on viability, expression of the antioxidant Nrf2, levels of the product of oxidative stress malondialdehyde (MDA), and the migration capacity of HGFs. MethodsAn experimental laboratory study used fibroblasts isolated from healthy human gingiva. The cells were grouped into the non-treatment control group (NTC), the solvent control (SC), and the treatment groups, exposed to nicotine at various concentrations for twenty-four hours. Cell viability was assesed using the cell counting kit-8 (CCK-8), Nrf2 expression was examined using ELISA, MDA level was measured using an MDA kit, and migration capacity was assessed using a scratch assay. Statistical analysis used one-way Anova or Kruskal-Wallis test. A p-value of <0.05 was expressed statistically significant. ResultsThe Cell viability was substantially reduced in the nicotine group compared to the untreated group, accompanied by changes in cell morphology. In contrast, Nrf2 expression increased significantly (p=0.010) in the 5 mM nicotine group compared with the control group. The MDA levels were not significantly distinct across groups (p=0.056). Cell migration was delayed significantly in the 5 mM nicotine group at 72 hours after scratching compared to the control group. ConclusionNicotine decreased HGFs viability and increased Nrf2 expression significantly in a dose-dependent manner. Nicotine at 5 mM concentration did not alter MDA levels but delayed cell migration.